IMPLEMENTASI KEBIJAKAN PEMANFAATAN ENERGI BARU TERBARUKAN (EBT) DALAM PEMENUHAN KEBUTUHAN LISTRIK DI DESA-DESA TERPENCIL DI SUMATERA UTARA (IMPLEMENTATION OF RENEWABLE ENERGY UTILIZATION POLICIES IN FULFILLMENT OF ELECTRICITY NEEDS AT ISOLATED VILLAGES) - Porman J.M Mahulae; Nobrya Husni (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
This study is a policy implementation study related to the utilization of Renewable Energy (EBT) in fulfilling electricity needs in remote villages in North Sumatra, wich considering into four important factors or variables in the implementation of a public policy: communication, Resources, dispositions or attitudes and bureaucratic structures. The approach used in this study is a descriptive qualitative approach by using in-depth interview data collection methods, participant observation, documentation and visual materials, internet search methods and Focus Group Discussion (FGD). While the analytical technique used is the constant comparative technique, which is one of the analytical techniques used in a research with a qualitative approach. This study concludes that the general problem in the implementation of electricity fulfillment policy in remote villages in north sumatera are: a) there is no detailed work plan for the utilization of EBT in fulfilling electricity needs in remote villages in North Sumatra; b) unavailability of valid data and information about potential EBT and number of villages without electricity; c) limited budget; And d) limited quality and quantity of human resources. Concrete steps proposed to be undertaken are: a) Preparation of Roadmap utilization of EBT potential in fulfilling electricity demand in North Sumatra; b) Periodical and ongoing inventory and mapping of EBT potentials, as well as the direction of EBT development; c) Education and dissemination of EBT-based potential and technology; and, d) Coordination between Central / Provincial / District / City Government, Society, Practitioner, Academician, and business world. Keywords: implementation of policies, electrical energy, remote villages, North Sumatra